Pentingnya Kemampuan Komunikasi Dalam Pelayanan Kesehatan - Has’ad Rahman Attamimi; Yunita Lestari; Nikodimus Margo Rinenggantyas (Compromise Journal Community Proffesional Service Journal, 2024)
Communication in health services is a supporting factor for health workers in expressing their roles and functions professionally. One of the competencies that must be possessed by medical personnel, whether doctors, nurses, midwives or other medical personnel, is the ability to communicate effectively and be easy to understand. Communication skills will underlie efforts to solve patient problems to facilitate the provision of assistance, both in medical and psychological services. These communication skills cannot simply be acquired without training. Therefore, this communication seminar in health services was carried out. This activity was attended by 271 students from various universities in Indonesia. The outcome of this seminar is to improve communication skills, especially for students, to become better. The activity which took place on January 25 2024 went very well. This was reflected in the enthusiasm of the participants in the discussion session. In the presentation session, the material was delivered by a practitioner and lecturer at the STIKES Griya Husada Sumbawa Nursing Study Program, Mr. Nikodimus Margo Rinenggantyas, S.Kep, Ns., M.Kep.